1997
DOI: 10.1183/09031936.97.10102230
|View full text |Cite
|
Sign up to set email alerts
|

Sustained protection against distilled water provocation by a single dose of salmeterol in patients with asthma

Abstract: In conclusion, a single dose of salmeterol induces both bronchodilatation and protection independently of this bronchodilation against a physiological bronchoconstrictor stimulus for more than 20 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…9 Following the administration of salmeterol at 1800 h, Fitzpatrick et al reported that the nocturnal pattern of airway tone was not affected despite significant bronchodilation, although the lack of standardisation of the night-time peak flow recordings limits interpretation of this observation. 21 In contrast, Bootsma et al reported that significant bronchodilation occurred at 20 (but not 34) h after a 50 mg dose of salmeterol delivered by MDI at 2200 h. 10 The magnitude of the difference in FEV 1 at 20 h with salmeterol compared with placebo was 10.4% of predicted values, similar to that observed in our study. No correlation was found between the bronchodilation and protection against provoked bronchoconstriction provided by salmeterol at any time point in this study, indicating that the protection of salmeterol is not predominantly caused by its bronchodilator activity.…”
Section: Article In Presssupporting
confidence: 85%
See 1 more Smart Citation
“…9 Following the administration of salmeterol at 1800 h, Fitzpatrick et al reported that the nocturnal pattern of airway tone was not affected despite significant bronchodilation, although the lack of standardisation of the night-time peak flow recordings limits interpretation of this observation. 21 In contrast, Bootsma et al reported that significant bronchodilation occurred at 20 (but not 34) h after a 50 mg dose of salmeterol delivered by MDI at 2200 h. 10 The magnitude of the difference in FEV 1 at 20 h with salmeterol compared with placebo was 10.4% of predicted values, similar to that observed in our study. No correlation was found between the bronchodilation and protection against provoked bronchoconstriction provided by salmeterol at any time point in this study, indicating that the protection of salmeterol is not predominantly caused by its bronchodilator activity.…”
Section: Article In Presssupporting
confidence: 85%
“…To date there have been few placebo-controlled studies of the bronchodilator time course of action over a 24 h period, following administration in the morning [7][8][9] and only a single study following evening administration. 10 However, if long-acting beta agonists are to be used once daily, it would seem preferable that they are administered in the evening to ensure that the maximum bronchodilator effect occurs during sleep when the enhanced circadian rhythm results in the greatest degree of bronchoconstriction. In this study we have investigated whether a single dose of the combination salmeterol/fluticasone (SFC) via an Accuhaler would significantly attenuate the circadian variation in airway tone and achieve bronchodilation for at least 24 h.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown that the effect of salmeterol on bronchodilation, protection against bronchial hyperresponsiveness, and other clinical measures exceed 12 h, suggesting that in some patients, salmeterol may exert therapeutic efficacy when given once daily. [8][9][10][11][12] Given the results obtained in some studies with once daily dosing with FP and other ICS, [13][14][15][16][17] together with studies demonstrating a duration of action of salmeterol exceeding 12 h, this study was conducted to determine the efficacy and safety of FP/salmeterol 250/50 mcg administered once daily in the evening (FSC 250/50 QD) compared with FP 250 mcg administered once daily in the evening (FP 250 QD), FSC 100/50 mcg administered twice daily (FSC 100/50 BID), or placebo (PLA) in symptomatic adolescent and adult patients with asthma using short-acting beta 2 -agonists alone. All treatments in this study were delivered via the Diskus s .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to evaluate the true offset of effect of these drugs beyond the 12 hour time point. A number of studies have shown that both salmeterol and formoterol have a long-lasting clinical efficacy after a single daily dose, which maintains significance above baseline at a 12 hour monitoring time point [ 12 , 13 , 18 - 25 ]. In the current study (study A), both SFC and FBC produced a similar prolonged bronchodilation beyond 12 hours which was statistically and clinically significant compared with placebo at 16 hours.…”
Section: Discussionmentioning
confidence: 99%